An inventory and topographic analysis of glaciers in the Torngat Mountains, northern Labrador, Canada. Issue 223 (2014) - Way, Robert G.; Bell, Trevor; Barrand, Nicholas E.
Abstract: This study presents the first complete glacier inventory of the Torngat Mountains, northern Labrador, Canada. In total, 195 glaciers and ice masses are identified, covering a total area of 24.5 ± 1.8 km 2 . Mapped ice masses range in size from 0.01 to 1.26 km 2, with a median size of 0.08 km 2 . Ice masses have a median elevation of 776 m a.s.l. and span an altitudinal range of 290–1500 m a.s.l. Indications of ice flow suggest at least 105 active glaciers in the Torngat Mountains. Analysis of morphometric and topographic parameters suggests that the regional distribution of ice masses is linked to physiographic setting while the preservation of coastal ice masses at low elevation is related to local meteorological conditions. In the most coastal environments, ice masses are shown to exist below the regional glaciation level due to topographic shadowing, coastal proximity and widespread debris cover. This study provides a baseline for future change assessment.